2017
DOI: 10.1016/j.nicl.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative measures of walking and strength provide insight into brain corticospinal tract pathology in multiple sclerosis

Abstract: At least 85% of individuals with multiple sclerosis report walking dysfunction as their primary complaint. Walking and strength measures are common clinical measures to mark increasing disability or improvement with rehabilitation. Previous studies have shown an association between strength or walking ability and spinal cord MRI measures, and strength measures with brainstem corticospinal tract magnetization transfer ratio. However, the relationship between walking performance and brain corticospinal tract mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 50 publications
5
50
1
1
Order By: Relevance
“…Conversely, the association between diffusivity in the frontal NAWM and disability as measured by the MS Functional Composite Scale has been found in primaryprogressive MS (Schmierer et al, 2004 We did not observe any associations in the IC between baseline DTI and disability progression. Our finding is supported by studies where no correlation between DTI indices in the corticospinal tract and disability progression expressed by an EDSS increase has been observed (Fritz, Keller, Calabresi, & Zackowski, 2017;Lin et al, 2007). This result indicates that diffusivity abnormalities may already exist in the IC, but they progress at different rates, and image disability progression distinctly than in the CC (Ge et al, 2004).…”
Section: Montag Giesser and Sicotte 2011) Moreover A Histogram-basedsupporting
confidence: 89%
See 1 more Smart Citation
“…Conversely, the association between diffusivity in the frontal NAWM and disability as measured by the MS Functional Composite Scale has been found in primaryprogressive MS (Schmierer et al, 2004 We did not observe any associations in the IC between baseline DTI and disability progression. Our finding is supported by studies where no correlation between DTI indices in the corticospinal tract and disability progression expressed by an EDSS increase has been observed (Fritz, Keller, Calabresi, & Zackowski, 2017;Lin et al, 2007). This result indicates that diffusivity abnormalities may already exist in the IC, but they progress at different rates, and image disability progression distinctly than in the CC (Ge et al, 2004).…”
Section: Montag Giesser and Sicotte 2011) Moreover A Histogram-basedsupporting
confidence: 89%
“…Conversely, the association between diffusivity in the frontal NAWM and disability as measured by the MS Functional Composite Scale has been found in primaryprogressive MS (Schmierer et al, 2004 (Ge et al, 2004). Our finding is supported by studies where no correlation between DTI indices in the corticospinal tract and disability progression expressed by an EDSS increase has been observed (Fritz, Keller, Calabresi, & Zackowski, 2017;Lin et al, 2007).…”
Section: Edss Median (Range)supporting
confidence: 77%
“…The networks associated with gait velocity in the DT condition demonstrated significantly greater FC in supplementary motor and prefrontal regions, when compared to the normal walking condition (Yuan et al, 2015). In persons with MS, two previous studies demonstrated that corticospinal motor pathway damage, measured using diffusion tensor imaging, was associated with walking performance (Hubbard et al, 2016, Fritz et al, 2017 in persons with MS. However, these studies did not examine the neural correlates of walking performance in persons with MS at the cortical level.…”
Section: Introductionmentioning
confidence: 81%
“…The symptomatic and neuroanatomic benefits of physical activity in MS are also evident. Cross-sectional studies in MS reveal positive associations between levels of physical activity and walking performance with fatigue, cognitive processing speed, brain volumes, and tract integrity (10)(11)(12). Longitudinal studies of aerobic exercise generally, although not invariably, demonstrate improvements in fitness and MS symptoms (3,13,14).…”
Section: Introductionmentioning
confidence: 99%